Analysis of adding-runs strategy for peak-hour regular bus services - An, Qinhe; Fu, Xiao; Huang, Di; Cheng, Qixiu; Liu, Zhiyuan (Transportation research. Part E, Logistics and transportation review, 2020)
•Proposing a new adding-runs strategy for peak-hour bus services to alleviate crowding effects.•Developing a bi-level programming model for the optimal adding-runs strategy.•User heterogeneity is considered in model formulation.•Examining the effectiveness of the proposed adding-runs strategy numerically. This paper proposes an adding-runs strategy to alleviate in-vehicle crowding for peak-hour bus services. Passengers’ departure time choices under user equilibrium and system optimum conditions are investigated with and without adding-runs strategy. A bi-level programming model is developed to determine the optimal adding-runs strategy. An artificial bee colony algorithm is adopted to solve the proposed bi-level problem. Numerical examples show that the adding-runs strategy is effective in alleviating crowding effects and reducing schedule delay in peak-hour bus services. The total system cost can be reduced by more than 8% with the optimal adding-runs strategy.